PERANCANGAN MESIN PENCACAH SAMPAH ORGANIK - Nuhgraha, Yoddy Agung; Abdi, Farhan; Damayanti, Eva (Jurnal TEDC, 2023)
This article is motivated by the issue of ineffective handling of organic waste that causes negative impacts on the environment, including air, water, and soil pollution. However, many people do not realize that organic waste has considerable potential to be used as useful and have added value with proper processing, for example such as processing organic waste as material for making compost.This article focuses on the design and estimation of organic waste shredding machines, which are an important tool for processing organic waste into smaller particles. This organic waste shredding machine has a primary function, namely as a tool to accelerate the process of shredding organic waste into smaller particles. The project begins by identifying needs, including determining the desired processing capacity, the type of organic waste to be chopped, material selection, component size and shredding particle size. Then a conceptual design is made that includes important aspects such as the manufacture of the frame and engine body, shafts and bearings, blade components, transmission systems. Computer-based design software (CAD) is used to create 2-dimensional and 3-dimensional models of organic waste shredding machine, thus enabling visualization and refinement of the design. Cost and time estimation are an important part of this project. The estimation includes factors such as material costs and also assembly fabrication costs. Time estimation describes the stages in the design process, as well as the production process of the organic waste shredding machine itself. The estimation includes factors such as material costs and also assembly fabrication costs. Time estimation describes the stages in the design process, as well as the production process of the organic waste shredding machine itself.The design and estimation process of this organic waste shredding machine produces a model of a organic waste shredding machine with a processing capacity of 1 kg, using the method of shredding blades shaped like propellers with a total of 24 blades, each of which has 3 blades. And there is a filter so that the shredding results have a size that is relevant to the size of compost in general, this organic waste enumeration process is supported by using an engine-powered gasoline engine with 5.6 HP that is transmitted to the shaft and a shredding blade through the pulley and v-belt transmission.